The impact of spousal bereavement on hospitalisations: Evidence from the Scottish Longitudinal Study. (22nd August 2017) - Tseng, Fu‐Min; Petrie, Dennis; Wang, Shaolin; Macduff, Colin; Stephen, Audrey I.
Abstract: This paper estimates the impact of spousal bereavement on hospital inpatient use for the surviving bereaved by following the experience of 94, 272 married Scottish individuals from 1991 until 2009 using a difference‐in‐difference model. We also consider the sample selection issues related to differences in survival between the bereaved and non‐bereaved using a simple Cox Proportional‐Hazard model. Before conducting these estimations, propensity score approaches are used to re‐weight the non‐bereaved to generate a more random‐like comparison sample for the bereaved. We find that those bereaved who survive are both more likely to be admitted and to stay longer in hospital than a comparable non‐bereaved cohort. Bereavement is estimated to induce on average an extra 0.24 (95% CI [0.15, 0.33]) hospital inpatient days per year. Similar to previous studies, we estimate the bereaved have a 19.2% (95% CI [12.5%, 26.3%]) higher mortality rate than the comparable non‐bereaved cohort.